1994
DOI: 10.1002/ajim.4700260605
|View full text |Cite
|
Sign up to set email alerts
|

Dose‐response relations between urinary cadmium and tubular proteinuria in cadmium‐exposed workers

Abstract: Cadmium in urine reflects the body burden in cadmium-exposed individuals. Urinary beta 2-microglobulin is frequently used as a marker of tubular proteinuria with an arbitrarily chosen value (34 micrograms/mmole creatinine) as the cut-off limit. Both this cut-off level and a lower limit (25 micrograms/mmole creatinine) were used in a study of the relationship between urinary cadmium and beta 2-microglobulin in 561 cadmium-exposed battery workers. There was a clear dose-response relation between the urinary cadm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 26 publications
0
8
0
3
Order By: Relevance
“…Cd-induced renal disease was found in 10% of an environmentally exposed Belgian population at urinary concentrations of only 2 to 3 μg Cd/g creatinine 14 . A study of 902 Swedish battery workers identified urinary β 2 microglobulin (a measure of tubular dysfunction) as an effective screening tool for early identification of Cd nephrotoxicity 15 . Prompt recognition and subsequent avoidance can prevent progression to ESRF 15, 16.…”
Section: Itai-itai Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Cd-induced renal disease was found in 10% of an environmentally exposed Belgian population at urinary concentrations of only 2 to 3 μg Cd/g creatinine 14 . A study of 902 Swedish battery workers identified urinary β 2 microglobulin (a measure of tubular dysfunction) as an effective screening tool for early identification of Cd nephrotoxicity 15 . Prompt recognition and subsequent avoidance can prevent progression to ESRF 15, 16.…”
Section: Itai-itai Diseasementioning
confidence: 99%
“…A study of 902 Swedish battery workers identified urinary β 2 microglobulin (a measure of tubular dysfunction) as an effective screening tool for early identification of Cd nephrotoxicity 15 . Prompt recognition and subsequent avoidance can prevent progression to ESRF 15, 16. No chelating agent has been identified, so renal replacement therapy remains the mainstay of treatment.…”
Section: Itai-itai Diseasementioning
confidence: 99%
“…Occupational exposure to cadmium was high during the 5 five decades of operation at the plant, but has gradually decreased since the 1960s 1011 Environmental cadmium pollution from these plants was substantial in the past, in particular in the vicinity of the Fliseryd plant. Here we present data on cadmium and early tubular effects whereas results from measurements of bone density are reported elsewhere 11…”
mentioning
confidence: 99%
“…One plant was closed in 1974, but the other is still operating. Occupational exposure to cadmium and lead was high during the first decades of plant operation, but has gradually decreased since the 1960s (16,17).…”
mentioning
confidence: 99%